Respostas
respondido por:
0
x + 6 = 25x² - 4
0 = 25x² - x - 4 - 6
0 = 25x² - x - 10
25x² - x - 10 = 0
a = 25; b = - 1; c = - 10
Δ = b² - 4ac
Δ = (-1)² - 4.25.(-10)
Δ = 1 + 1000
Δ = 1001
x = - b +/- √Δ = - (-1) +/- √1001
--------------- ---------------------
2a 2.25
x' = 1 + √1001
---------------
50
x" = 1 - √1001
---------------
50
0 = 25x² - x - 4 - 6
0 = 25x² - x - 10
25x² - x - 10 = 0
a = 25; b = - 1; c = - 10
Δ = b² - 4ac
Δ = (-1)² - 4.25.(-10)
Δ = 1 + 1000
Δ = 1001
x = - b +/- √Δ = - (-1) +/- √1001
--------------- ---------------------
2a 2.25
x' = 1 + √1001
---------------
50
x" = 1 - √1001
---------------
50
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás